Pengaruh Motivasi Kerja, Pelatihan dan Disiplin Kerja terhadap Kinerja Pegawai Badan Perencanaan Pembangunan Penelitian dan Pengembangan Daerah Kabupaten Brebes - Eva Lutfiyatul Latipah; Slamet Bambang Riono; Dumadi Dumadi; M. Badrun Zaman; Gian Fitrialisma (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The low performance of employees, which is caused by suboptimal work motivation, training programs that are not fully relevant to job requirements, and inconsistent discipline, remains a major issue. This condition is also evident at the Regional Planning, Research, and Development Agency (Baperlitbangda) of Brebes Regency, where several employees have shown work delays, lack of initiative, and training programs that are not well-targeted. This study aims to analyze the effect of work motivation, training, and work discipline on the performance of employees at Baperlitbangda Brebes. This research employed a quantitative approach with an explanatory method. The population consisted of all 50 employees of Baperlitbangda, and due to the relatively small population size, a saturated sampling technique was applied so that the entire population was included as research respondents. Data were collected through observation, interviews, and questionnaires using a Likert scale, and analyzed using multiple linear regression with SPSS. The results of the study indicate that work motivation has a positive and significant effect on employee performance. Training also shows a positive and significant effect, suggesting that relevant training materials, competent instructors, and appropriate methods can enhance productivity. Work discipline significantly affects performance, particularly through compliance with regulations, punctuality, and responsibility. Simultaneously, the three independent variables have a significant positive effect on employee performance. Work motivation, training, and discipline are crucial factors that must be taken into consideration in improving employee performance in the public sector. The practical implication of this study is that the management of Baperlitbangda Brebes needs to strengthen its reward system, improve the quality of training, and enforce disciplinary rules to enhance organizational performance